Más acá del Colorado… Historia regional y relaciones fronterizas en la norpatagonia argentina: el caso de Neuquén - Susana Bandieri (Centre de Recherches sur les Mondes Américains, 2012)
The province of Neuquén is located in northwest Patagonia region of Argentina. There, landlocked conditions and isolation conferred a special uniqueness to the territory. The Andes, with its special accessibility was used historically, from the earliest stages of indigenous occupation, like the backbone of an socially and economically integration in between the provinces of southern Chile and Argentina. That region survived over the political and administrative boundaries fixed on  the territory from the times of its military conquest. This resulted in the historical process, wher Neuquen become in a regional specialization with its own operation and exchange. That scheme and a consistent socio-spatial organization supports differential treatment. In fact, it’s no possible to think the history of the region paying atention to their territorial limits only. Considering the importance of  a frontier area where existence itself is defined historically, particularly as an social space for it long terme and high complexity, should be of the highest interest.